2019
DOI: 10.3390/catal9121012
|View full text |Cite
|
Sign up to set email alerts
|

Lipase Catalyzed Acidolysis for Efficient Synthesis of Phospholipids Enriched with Isomerically Pure cis-9,trans-11 and trans-10,cis-12 Conjugated Linoleic Acid

Abstract: The production of phospholipid (PL) conjugates with biologically active compounds is nowadays an extensively employed approach. This type of phospholipids conjugates could improve bioavailability of many poorly absorbed active compounds such as isomers of conjugated linoleic acid (CLA), which exhibit versatile biological effects. The studies were carried out to elaborate an efficient enzymatic method for the synthesis of phospholipids with pure (>90%) cis-9,trans-11 and trans-10,cis-12 CLA isomers. For this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Verdasco-Martín, et al [24] reported that using a PC sample without dehydration severely affected reaction efficiency caused by undesired hydrolysis and strongly competes with the desired esterification of FAs. This could be caused by existing water in the substrates or water produced in the reaction adequate to maintain lipase activity in the reaction [33,34]. Li, et al [35] reported that a hydrolysis reaction occurred even though the water addition was 0% wt which may be contributed by the inherent moisture of the immobilized PLA 1 that results in the continued decrease in PC recovery.…”
Section: Water Contentmentioning
confidence: 99%
“…Verdasco-Martín, et al [24] reported that using a PC sample without dehydration severely affected reaction efficiency caused by undesired hydrolysis and strongly competes with the desired esterification of FAs. This could be caused by existing water in the substrates or water produced in the reaction adequate to maintain lipase activity in the reaction [33,34]. Li, et al [35] reported that a hydrolysis reaction occurred even though the water addition was 0% wt which may be contributed by the inherent moisture of the immobilized PLA 1 that results in the continued decrease in PC recovery.…”
Section: Water Contentmentioning
confidence: 99%
“…On one hand, the presence of water in the reaction system is crucial for the hydrolysis of PLs and the activation of the enzyme. On another hand, under high content or activity of water, the additional moisture may either decrease the catalytic of the enzyme or lead to undesired hydrolysis reactions [30,63].…”
Section: Water Content/activitymentioning
confidence: 99%
“…Levels of water addition also affected reaction time where the incorporation reached its maximum under a given water dosage and the final composition of the products. Niezgoda and Gliszczynska [30] investigated the effect of water activity on the efficiency of PC acidolysis with conjugated linoleic acid (CLA) under the condition of a w = 0.11, 0.23, and 0.33. They found that the effective incorporation of CLA declined in the series 0.23 > 0.33 > 0.11.…”
Section: Water Content/activitymentioning
confidence: 99%
“…It has high activity and regioselectivity. Depending on reaction conditions, CalB can promote reactions such as hydrolysis and acidolysis [ 7 , 8 , 9 , 10 , 11 ]. CalB is expected to be a non-toxic and renewable energy source.…”
Section: Introductionmentioning
confidence: 99%